2007
DOI: 10.1111/j.1745-4581.2007.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

VALIDATION OF YEAST IDENTIFICATION BY IN SILICO RFLP

Abstract: Reliability, high reproducibility and high throughput are advantages of genetic identification methods over conventional methods based on phenotypic characteristics. In our work, we showed that the PCR‐RFLP of internal transcribed spacer (ITS) of ribosomal DNA (rDNA) method can be a very powerful identification or validation method, if it is combined with computer‐based restriction analysis of sequences stored in broadening databases. We isolated 197 yeast samples from grape berries and fermenting grape must a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…We sought to analyze the intra-species genetic variation of marula isolates, which showed a significantly high percentage of similarity of their ITS1-5.8S-ITS4 region. In-Silico PCR-RFLP restriction patterns are comparable to restriction patterns obtained in vitro (Raspor et al 2007 ). The precision of discrimination of PCR-RFLP has been considered to be parallel to sequencing analysis and therefore as an alternative method for species identification and delimitation (Pham et al 2011 , da Fonseca Meireles et al 2022 ) and the better option in instances where rapid validation or identification is needed considering its simplicity, speed, high reproducibility and high throughput (Raspor et al 2007 ).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…We sought to analyze the intra-species genetic variation of marula isolates, which showed a significantly high percentage of similarity of their ITS1-5.8S-ITS4 region. In-Silico PCR-RFLP restriction patterns are comparable to restriction patterns obtained in vitro (Raspor et al 2007 ). The precision of discrimination of PCR-RFLP has been considered to be parallel to sequencing analysis and therefore as an alternative method for species identification and delimitation (Pham et al 2011 , da Fonseca Meireles et al 2022 ) and the better option in instances where rapid validation or identification is needed considering its simplicity, speed, high reproducibility and high throughput (Raspor et al 2007 ).…”
Section: Resultssupporting
confidence: 68%
“…In-Silico PCR-RFLP restriction patterns are comparable to restriction patterns obtained in vitro (Raspor et al 2007 ). The precision of discrimination of PCR-RFLP has been considered to be parallel to sequencing analysis and therefore as an alternative method for species identification and delimitation (Pham et al 2011 , da Fonseca Meireles et al 2022 ) and the better option in instances where rapid validation or identification is needed considering its simplicity, speed, high reproducibility and high throughput (Raspor et al 2007 ). While da Fonseca Meireles et al ( 2022 ) used one restriction enzyme to differentiate yeasts of different genera and species, here we further increase the precision by using multiple restriction enzyme to differentiate within strains .Single restriction enzymes often have poor resolution (similar restriction profiles) in differentiating closely similar sequences of strains, we further revealed that use of a combination of different restriction enzymes was sufficient to resolve the genetic differences.…”
Section: Resultssupporting
confidence: 68%
“…AF075498); Fell et al, 2000], and for those, the sequencing of the ITS1-5.8S rRNA gene-ITS2 regions was required. Further, the species identities were confirmed by in silico RFLP of the ITS regions using the PDRAW 1.0 software (Kjeld, 2006) as suggested by Raspor et al (2007). We isolated 24 species belonging to 13 genera, of which nine belonged to basidiomycetous yeasts, mainly red-pigmented species of Rhodotorula and Sporidiobolus and nonpigmented or lightly pigmented Cryptococcus sp.…”
Section: Ecological Factors Affecting Yeast Diversitymentioning
confidence: 97%
“…One is limited to the forecast of electrophoretic patterns [8], the other presents a program to assess the utility of a fixed set of endonucleases to distinguish between a given set of sequences [14]. However, the integration of all the available data in a comprehensive in silico approach, targeting optimality in identification by ARDRA is still to be proposed.…”
Section: Introductionmentioning
confidence: 99%